2015
DOI: 10.1111/papr.12312
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy: A New Treatment for Chronic Pain?

Abstract: HBOT has been shown to reduce pain using animal models. Early clinical research indicates HBOT may also be useful in modulating human pain; however, further studies are required to determine whether HBOT is a safe and efficacious treatment modality for chronic pain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 35 publications
2
31
0
3
Order By: Relevance
“…The antinociceptive efficacy of HBO treatment has been proven in many rodent experiments and also human patients [911, 13]. In accordance with these findings, our current study demonstrated that five consecutive days of HBO treatment greatly attenuated neuropathic pain by suppressing hypersensitivity in rats following CCI of the sciatic nerve.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The antinociceptive efficacy of HBO treatment has been proven in many rodent experiments and also human patients [911, 13]. In accordance with these findings, our current study demonstrated that five consecutive days of HBO treatment greatly attenuated neuropathic pain by suppressing hypersensitivity in rats following CCI of the sciatic nerve.…”
Section: Discussionsupporting
confidence: 89%
“…HBO treatment has been recognized as a promising non-invasive therapy for a variety of disorders, including neuropathic pain [9]. The antinociceptive efficacy of HBO treatment has been proven in many rodent experiments and also human patients [911, 13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBOT treatment has been done for patients with chronic pain syndromes with excellent effectiveness (42). Sutherland et al indicated that HBOT is useful in modulating animal and human pain (43). In our systematic review, the efficacy of HBOT in healing and improving general health, daily activity, emotional problems, and body pain in patients was confirmed (15).…”
Section: Fibromyalgiamentioning
confidence: 85%
“…Clinically, some advances in the treatment of chronic pain have been reported [5–7]. In animal models, HBO has been reported to effectively relieve inflammatory pain [8].…”
Section: Introductionmentioning
confidence: 99%